Diagnostico de las zonas fronterizas de consolidación: análisis de la gestión pública territorial, en el periodo 2005-2010 (2012)
This paper aims to develop a diagnosis of the border areas of consolidation, in order to analyze the factors that have influenced the management of territorial governments in the period 2005-2010, and in turn to propose and develop strategies for resolving the social problem that afflicts the civilians in these particular areas. Shall be based on the Integral Performance Index of Municipal Management, developed by the National Planning Department, which allows evaluation of municipal management in four integrated components: effectiveness, efficiency, management, environment and compliance with legal requirements. The results show a critical Integral Performance Index of Municipal Management, in these territories.